THE EFFECT OF THE IMPLEMENTATION OF GREEN ACCOUNTING AND ENVIRONMENTAL PERFORMANCE ON COMPANY VALUE - Endah Supeni Purwaningsih; Rodhiyah; Pramandyah Fitah Kusuma; Pujianto (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2026)
Indonesia is currently facing climate change due to global warming caused by various human activities that can threaten environmental sustainability. Most of the causes of climate change occur due to the combustion of non-renewable energy sources, such as oil, gas, and coal. A company is not only responsible for generating maximum profits but also responsible for all impacts caused by its operational activities on society and the environment. This study aims to examine and analyze the effect of the implementation of green accounting and environmental performance on company value in energy and basic material sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This type of research is causal research with a quantitative approach. The sample in this study amounted to 42 obtained from 14 energy and basic material sector companies listed on the IDX with a research period of 3 years. The results show that green accounting and environmental performance do not affect company value, either partially or simultaneously in energy and basic material sector companies listed on the IDX for the period 2021-2023. In this study, company value is proxied using Tobin's Q